Selective Current Compensators Based on the Conservative Power Theory - Paredes, Helmo K. M.; Marafao, Fernando P.; Silva, Luiz C. P. da [UNESP]; Toma, L.; Otomega, B. (Ieee, 2009)
This paper presents possible selective current compensation strategies based on the Conservative Power Theory (CPT). This recently proposed theory, introduces the concept of complex power conservation under non-sinusoidal conditions. Moreover, the related current decompositions results in several current terms, which are associated with a specific physical phenomena (power absorption P, energy storage Q, voltage and current distortion D). Such current components are used in this work for the definition of different current compensators, which can be selective in terms of minimizing particular disturbing effects. The choice of one or other current component for compensation directly affects the sizing and cost of active and/or passive devices and it will be demonstrated that it can be done to attend predefined limits for harmonic distortion, unbalances and/or power factor. Single-phase compensation strategies will be discussed by means of the CPT and simulation results will demonstrate their performance.